Aristotle and his Vision of indroduction of Coinage in Ancient Greek World - Jankowska, Aleksandra (Acta Archaeologica Lodziensia, 2021)
Famous statement proposed by Aristotle that the first coinage was introduced for the needs of trade became the dominant and universally favoured view. However, the ideas of the philosopher seem to be more sophisticated and complex. In fact, Aristotle considers the origin of coinage in two different works, the Nicomachean Ethics and the Politics. The first one concentrates on the meaning of commerce and wealth and on exchange within the polis. The other focuses on the origin of the state and considers both the role of coins in the development of the polis and money as a medium of exchange between states. Coinage emerges not merely as a medium of commercial exchange but also as a part of civic and political reciprocity, as a conventional sign. It is important to understand these different contexts and to put them in the wider ideological and philosophical discursive perspective.